The use of social media to drive the growth of South African brands - Reddy, Nishanta (University of the Witwatersrand, Johannesburg, 2023)
The proliferation of social media usage has coincided with the expansion of social media marketing efforts. However, the mere escalation in social media activity does not uniformly translate into user interaction or engagement with advertisements disseminated through these platforms. Consequently, it becomes imperative to scrutinize the determinants of engagement and discern how such engagement can impact the development of indigenous South African brands. Existing scholarly literature offers limited insights into the factors underpinning social media brand engagement and the resultant effects on the advancement of local brands within the South African market. This research aims to augment the Customer-Based Brand Equity (CBBE) model with the aim of delineating the catalysts propelling engagement with social media brands and investigating the ramifications of such engagement on the performance metrics of domestic brands. Employing a quantitative methodology, the study leveraged an online survey to solicit responses from 272 South African social media users. The findings underscore that the principal determinants of social media brand engagement encompass entertainment value, brand resonance, informativeness, and social influence. Furthermore, the analysis reveals those interactions with brand advertisements on social media platforms bolster purchase intent, thereby fostering an amelioration in brand performance metrics. This emphasizes the pivotal role played by social media platforms in fostering the growth of local brands in South Africa. Consequently, social media engagement emerges as a pivotal determinant shaping the trajectory of growth and performance for local brands, underscoring the imperative of deploying strategic social media marketing initiatives tailored to the specificities of the South African market landscape.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Social media marketing; South Africa; Local brands; Social media engagement; UCTD; SDG-8: Decent work and economic growth